Olive cultivation in ancient Greece : seeking the ancient economy - Foxhall, Lin (Oxford University Press, 2007)
An examination of olive cultivation as a way of understanding ancient Greek agriculture in its landscape, economic, social, and political settings. Lin Foxhall assembles evidence from written sources, archaeology, and visual images. Her investigation opens up new ways of thinking about the economies of the archaic and classical Greek world. - ;Lin Foxhall explores the cultivation of the olive as an extended case study for understanding ancient Greek agriculture in its landscape, economic, social, and political settings. Evidence from written sources, archaeology, and visual images is assembled.